(De)colonizing the Italian South: Transcultural narrations and geopolitical dislocations in Carlo Levi - Binetti, Vicenzo (Spunti e Ricerche, 2025)
The article contains brief reﬂections on a text that eludes any rigid classiﬁcation: Christ Stopped at Eboli. The author does not intend to probe into coeval diatribes tied to the reception and contribution of the novel but aĴempts to understand how this text could help us today to problematize the South of Italy and the various ‘souths’ of our planet within a global discourse.